Characteristics of patients associated with any outpatient antibiotic prescribing among Medicare Part D enrollees, 2007-2018 - Christine Y. Kim; Katryna A. Gouin; Lauri A. Hicks; Sarah Kabbani (Cambridge University Press, 2023)
The 2007-2018 National Health Interview Survey data linked with Medicare claims were used to examine older adults' characteristics and assess their associations with receiving an antibiotic prescription. This analysis shows variation in antibiotic prescribing among adults enrolled in Medicare Part D by race and ethnicity, sex, geography, and health status.